Cardiovascular risk factors and target organ damage in hypertensive patients at Hue University of Medicine and Pharmacy Hospital - Duong, Minh Quy; Hoang, Anh Tien; Doan, Khanh Hung (Tạp chí Y Dược Huế, 2025)
Background: Hypertension is one of the most common cardiovascular diseases, often referred to as the silent killer. The prevalence of hypertension is increasing globally. This study investigates certain clinical and subclinical characteristics, cardiovascular risk factors in hypertensive patients, and evaluates the correlation between these risk factors and target organ damage with systolic and diastolic blood pressure. Subjects and methods: This was a cross-sectional descriptive study of hypertensive patients treated at Hue University of Medicine and Pharmacy Hospital from January 1, 2024, to December 31, 2024. Results: The study included 215 hypertensive patients, with a blood pressure control rate of 35.8%. Patients whose blood pressure was controlled had a younger age, lower BMI, a lower incidence of smoking, lower LDL-C levels, and lower rates of cerebrovascular accidents and diabetes, all showing statistical significance compared to the uncontrolled group. The high cardiovascular risk group had higher blood glucose and lower HDL-C levels, both statistically significant compared to the low cardiovascular risk group. A moderate positive correlation was found between systolic blood pressure and smoking, a strong positive correlation between systolic blood pressure and blood glucose, and a moderate positive correlation between systolic blood pressure and the Gensini score. Conclusion: There is a correlation between cardiovascular risk factors and blood pressure control. Achieving target blood pressure helps reduce the risk of target organ damage.